Trans*: A quick and quirky account of gender variability - Halberstam, Jack (American studies now : critical histories of the present, 2018)
In the last decade, public discussions of transgender issues have increased exponentially. However, with this increased visibility has come not just power, but regulation, both in favor of and against trans people. What was once regarded as an unusual or even unfortunate disorder has become an accepted articulation of gendered embodiment as well as a new site for political activism and political recognition. What happened in the last few decades to prompt such an extensive rethinking of our understanding of gendered embodiment? How did a stigmatized identity become so central to U.S. and European articulations of self? And how have people responded to the new definitions and understanding of sex and the gendered body? In Trans*, Jack Halberstam explores these recent shifts in the meaning of the gendered body and representation, and explores the possibilities of a nongendered, gender-optional, or gender-queer future.
Keywords: approches et analyses; corps; cours; fem3200; identités LGBTQIA2+; personnes trans*; premier cycle; queer; ressource en ligne; thématiques; transféminisme

In a queer time and place: Transgender bodies, subcultural lives - Halberstam, Jack (J.) (New York University Press, 2005)
In a Queer Time and Place opens with a probing analysis of the life and death of Brandon Teena, a young transgender man who was brutally murdered in small-town Nebraska. After looking at mainstream representations of the transgender body as exhibited in the media frenzy surrounding this highly visible case and the Oscar-winning film based on Brandon's story, Boys Don’t Cry, Halberstam turns her attention to the cultural and artistic production of queers themselves. Halberstam examines the “transgender gaze,” as rendered in small art-house films like By Hook or By Crook, as well as figurations of ambiguous embodiment in the art of Del LaGrace Volcano, Jenny Saville, Eva Hesse, Shirin Neshat, and others. Halberstam then exposes the influence of lesbian drag king cultures upon hetero-male comic films, such as Austin Powers and The Full Monty, and, finally, points to dyke subcultures as one site for the development of queer counterpublics and queer temporalities. Considering the sudden visibility of the transgender body in the early twenty-first century against the backdrop of changing conceptions of space and time, In a Queer Time and Place is the first full-length study of transgender representations in art, fiction, film, video, and music. This pioneering book offers both a jumping off point for future analysis of transgenderism and an important new way to understand cultural constructions of time and place.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; cinéma; communication; cours; discipline; fem1000; har4600; identités LGBTQIA2+; lit4700; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme; états-unis; études culturelles

The queer art of failure - Halberstam, Jack (J.) (Duke University Press., 2011)
The Queer Art of Failure is about finding alternatives—to conventional understandings of success in a heteronormative, capitalist society; to academic disciplines that confirm what is already known according to approved methods of knowing; and to cultural criticism that claims to break new ground but cleaves to conventional archives. Jack Halberstam proposes “low theory” as a mode of thinking and writing that operates at many different levels at once. Low theory is derived from eccentric archives. It runs the risk of not being taken seriously. It entails a willingness to fail and to lose one’s way, to pursue difficult questions about complicity, and to find counterintuitive forms of resistance. Tacking back and forth between high theory and low theory, high culture and low culture, Halberstam looks for the unexpected and subversive in popular culture, avant-garde performance, and queer art. Halberstam pays particular attention to animated children’s films, revealing narratives filled with unexpected encounters between the childish, the transformative, and the queer. Failure sometimes offers more creative, cooperative, and surprising ways of being in the world, even as it forces us to face the dark side of life, love, and libido.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; fem1000; genre; har4600; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; régions géographiques; thématiques; états-unis; études culturelles

Avoir l’air butch. Une esquisse de guide sur les butches au cinéma. Partie 1/2 - Halberstam, Jack (Genre en séries, 2019)
Nous proposons ici la première partie de ce chapitre. La partie 2 sera publiée dans le prochain numéro de Genre en séries : cinéma, télévision, cinéma. Le prénom Jack a été choisi ici parce que Halberstam tend à le privilégier depuis ses recherches sur les drag kings (http://www.lambdaliterary.org/interviews/02/01/jack-halberstam-queers-create-better-models-of-success/), tout en insistant sur sa volonté de ne pas résoudre son ambiguïté genrée (« my floating gender pronouns capture well the refusal to resolve my gender ambiguity that has become a kind of identity for me »). Voir http://www.jackhalberstam.com/on-pronouns/
Keywords: 1900-1999; amériques; approches et analyses; cinéma; communication; discipline; hétérosexisme; identités LGBTQIA2+; périodes historiques; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; états-unis

Technotopies : La représentation des corps transgenres dans l'art contemporain - Halberstam, Jack (J.) (La rébellion du deuxième sexe : l'histoire de l'art au crible des théories féministes anglo-américaines (1970-2000), 2011)
Keywords: 1900-1999; amériques; approches et analyses; art contemporain; corps; cours; discipline; fem1000; identités LGBTQIA2+; personnes trans*; premier cycle; périodes historiques; régions géographiques; technologie; thématiques; états-unis